Case Report: Persisting Lymphopenia During Neuropsychiatric Tumefactive Multiple Sclerosis Rebound Upon Fingolimod Withdrawal - Koska, Valeria; Förster, Moritz; Brouzou, Katja; Arat, Ercan; Albrecht, Philipp; Aktas, Orhan; Küry, Patrick; Meuth, Sven G.; Kremer, David (Frontiers in Neurology, 2021)
Fingolimod (FTY) is a disease modifying therapy for relapsing remitting multiple sclerosis (RRMS) which can lead to severe lymphopenia requiring therapy discontinuation in order to avoid adverse events. However, this can result in severe disease reactivation occasionally presenting with tumefactive demyelinating lesions (TDLs). TDLs, which are thought to originate from a massive re-entry of activated lymphocytes into the central nervous system, are larger than 2 cm in diameter and may feature mass effect, perifocal edema and gadolinium enhancement. In these cases, it can be challenging to exclude important differential diagnoses for TDLs such as progressive multifocal leukoencephalopathy (PML) or other opportunistic infections. Here, we present the case of a 26-year-old female patient who suffered a massive rebound with TDLs following FTY discontinuation with primarily neuropsychiatric symptoms despite persisting lymphopenia. Two cycles of seven plasmaphereses each were necessary to achieve remission and ocrelizumab was used for long-term stabilization.